2016
DOI: 10.14393/bj-v32n2a2016-29753
|View full text |Cite
|
Sign up to set email alerts
|

Production and nutritional characteristics of sunflowers and paiaguas palisadegrass under different forage systems in the off season

Abstract: ABSTRACT:The high efficiency of sunflowers in extracting water from the soil under water stress conditions is a factor that promotes sunflower cultivation in the offseason. Therefore, sunflowers have been intercropped with grasses of the Urochloa genus in crop-livestock integration systems. However, little is known of sowing methods for intercropping; thus, the present study aimed to assess sunflower agronomic traits and the production and nutritional characteristics of Paiaguas palisadegrass under different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
(2 reference statements)
2
5
0
Order By: Relevance
“…Coefficients of variance (CV) for agronomic characteristics of the sunflower were classified low or average, following classification suggested by Pimentel-Gomes (2009). They were similar to those reported by Souza et al (2015) and Santos et al (2016), who evaluated the agronomic characteristics of the sunflower intercropping species of the genus Urochloa.…”
Section: Resultssupporting
confidence: 90%
“…Coefficients of variance (CV) for agronomic characteristics of the sunflower were classified low or average, following classification suggested by Pimentel-Gomes (2009). They were similar to those reported by Souza et al (2015) and Santos et al (2016), who evaluated the agronomic characteristics of the sunflower intercropping species of the genus Urochloa.…”
Section: Resultssupporting
confidence: 90%
“…Nitrogen and potassium are the two nutrients most absorbed by forage plants (Costa et al, 2016(Costa et al, , 2017, and in the present study, they were found in greater abundance in the Paiaguas palisadegrass and Tamani guinea grass biomasses. The phosphorus, potassium and sulphur accumulation was satisfactory in the biomass of the Paiaguas palisadegrass and Tamani guinea grass cropping systems for the uptake required by soybean as a successor crop, showing that these forages can release amounts close to the crop needs.…”
Section: Discussionsupporting
confidence: 64%
“…Grazing animals in an integrated crop-livestock system can modify nutrient and plant residue cycling rates, changing the biochemical form of nutrients, their spatial distribution within the pasture, and their time of release or availability (Assmann et al, 2017) via their return in manure and urine. In this sense, animals act as nutrient recycling agents (Carvalho et al, 2010), which may result in a lesser need for fertilizer for the next crop and maintenance of production sustainability over time (Costa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations